Mayan language revitalization, hip hop, and ethnic identity in Guatemala. (March 2016) - Barrett, Rusty
Abstract: This paper analyzes the language ideologies and linguistic practices of Mayan-language hip hop in Guatemala, focusing on the work of the group B'alam Ajpu. The members of B'alam Ajpu use a mix of Spanish and Mayan languages in their music and run a school that combines lessons in hip hop (rapping, break-dancing, etc.) with efforts to promote the use of Mayan languages among children. The language ideologies associated with B'alam Ajpu intersect and challenge the ideologies associated with both language revitalization and with hip hop. The linguistic practices of B'alam Ajpu also challenge hegemonic assumptions regarding ethnic identity in Guatemala. Highlights: Mayan language hip hop in Guatemala has emerged as part of language revitalization efforts. The use of Mayan languages in hip hop challenges the dominant language ideologies in Guatemala. In the context of language revitalization, Maya hip hop challenges understandings of both indigenous and non-indigenous identities.